2017
DOI: 10.1126/sciadv.1603141
|View full text |Cite
|
Sign up to set email alerts
|

Quantum coherence as a witness of vibronically hot energy transfer in bacterial reaction center

Abstract: Observation of coherence shifts reveals hot energy transfer and excess energy dissipation mechanisms in photosynthesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 41 publications
4
102
0
Order By: Relevance
“…These resonances lead to inseparability of nuclear and electronic degrees of freedom (96,97), which some theoretical work has suggested may affect energy transfer (98). These resonances have also been reported in photosynthetic reaction centers (89,99,100). Yet, the character of a quantum state, which is initially strongly vibronic in nature, changes over time in a nontrivial way when the electronic and vibrational sectors are exposed to different dephasing and relaxation channels on very different time scales.…”
Section: Present Status Of Experiments: Revisiting Fmomentioning
confidence: 87%
See 1 more Smart Citation
“…These resonances lead to inseparability of nuclear and electronic degrees of freedom (96,97), which some theoretical work has suggested may affect energy transfer (98). These resonances have also been reported in photosynthetic reaction centers (89,99,100). Yet, the character of a quantum state, which is initially strongly vibronic in nature, changes over time in a nontrivial way when the electronic and vibrational sectors are exposed to different dephasing and relaxation channels on very different time scales.…”
Section: Present Status Of Experiments: Revisiting Fmomentioning
confidence: 87%
“…In the presence of vibronic mixing of electronic and vibrational stateswhich seems to be the case in many photosynthetic complexescoherence signals are very much entangled, and an oscillation map analysis (Fig. 4) is indispensable (89). To outline a basic framework for the interpretation of QBs in 2D spectra and to provide readers with some basic tools to qualitatively assess 2D experiments on QBs, we schematically show their analysis in two relevant model systems in Fig.…”
Section: Studies Of Photosynthetic Excitonsmentioning
confidence: 99%
“…Obviously, since the detected oscillation signals originate from all the possible Liouville pathways including the excitonic and single-mode or multi-mode vibrationally coupled coherences, new methods either of apparatus or data analysis are called for clear distinguishing the electronic coherence from those of vibronic. It has been shown that the polarization modulated [67,68] 2DES can be an effective way toward this purpose as successfully demonstrated in a recent experiment, where the oscillation maps extracted from the doublecross polarized schemes (relative polarizations of π/4, −π/4, π/2, and 0 for laser pulses 1 to 4) strongly suppresses signals of intramolecular vibrational coherences produced by the Franck-Condon excitation of vibrational wave packets [69]. On the other hand, 2D singletime-domain exciton perturbation spectroscopy (2D-STEPS) and 2D time-resolved interexciton perturbation spectroscopy (2D-TRIPS) are the new approaches to extract information from 2DES spectra.…”
Section: Single-vibrational Mode Versus Multi-vibrational Mode Coumentioning
confidence: 92%
“…sphaeroides RC. 46 On the basis of this mechanism, the 33 and 153 cm –1 oscillations can be assigned to excited-state vibronic coherence followed by a shift into the ground-state vibrational coherence. The assignment of the 235 cm –1 oscillations was not as definite as the 33 and 153 cm –1 ones.…”
mentioning
confidence: 98%